Ethnoarchaeological Perspectives on an Athapaskan Moose Kill - Jarvenpa, Robert; Brumbach, Hetty Jo (ARCTIC, 1983)
A recent development in anthropology involves examination of living human populations in an attempt to better understand the "formation processes" that create archaeological remains. An ethnologist and an archaeologist collaborated in the observation and analysis of procurement, butchering and distribution of moose among a group of contemporary Athapaskan (Chipewyan) Indians in northwestern Saskatchewan in 1977. Subtleties in the behavior of one particular hunting party illustrate the complexity and variability of skeletal and anatomical spatial distributions accompanying various stages in processing, distributing and consuming a moose (Alces alces andersoni). Variables such as seasonality, proximity to a major settlement, transportation technology, sexual division of labor and ideational factors heavily influence the formation of archaeo-faunal remains within several components of a regional settlement system.Key words: ethnoarchaeology, Chipewyan Indians, moose hunting, decision making, site formation Une recherche anthropologique récente comporte l'étude de populations vivantes en visant une meilleure compréhension des processus qui forment les restes archéologiques. Une ethnologue et un archéologue ont collaboré dans l'observation et l'analyse des méthodes d'obtention, de boucherie et de distribution d'orignal au sein du'une groupe contemporain d'indiens athapascans (Chipewyans) dans le nord-ouest de la Saskatchewan. Les subtilités dans le comportement d'un groupe particulier de chasseurs démontrent la complexité et la variabilité des distributions spatiales anatomiques et squelettiques suivant les diverses étapes du dépeçage, de la distribution et de la consommation d'un orignal (Alces alces andersoni). Des variables telles que le caractère saisonnier, la proximité à un site majeur d'habitation, la technologie du transport et I'ingéniosité influencent de façon importante la formation de restes archéologiques animaux dans de nombreuses composantes d'une habitation régionale.Mots clés: ethnoarchéologie, ...